Web 2.0 Tools: A mediation in the teaching and learning process of mathematics and physics in higher education (2020)
The objective was to design a didactic experience that would facilitate the processes of teaching and learning of functions in the students of a public university. A quantitative approach is adopted at the descriptive level. The questionnaire is used as an instrument. As a result, it was found that the activities implemented facilitated the learning of mathematics applied to physics. The contributions are concluded as positive since the students were able to focus on specific aspects of the selected lessons applying physical reasoning by means of the Web 2.0 resource.